Post-transcriptional regulation of microRNAs in cancer: from prediction to validation - Sheril June Ankasha; Mohamad Nasir Shafiee; Norhazlina Abdul Wahab; Raja Affendi Raja Ali; Norfilza Mohd Mokhtar (Frontiers Media S.A., 2018)
MicroRNA (miRNA) is a small non-coding RNA with an established function to regulate genes at the post-transcriptional level leading to suppression or degradation of its messenger RNA expression (mRNA). Its dysregulation plays a vital role in a variety of biological and pathological processes including cancer. A lot of algorithms have been established to predict the target sites of miRNA, but experimentally identifying and validating its target region is still lacking. Guidance in experimental procedures is really needed to find genuine miRNA targets. Therefore, in this review, we provide an outline on the workflow in predicting and validating the targeted sites of miRNA using several methods as a guideline for the scientists. The final outcome of this type of experiment is essential to explore the major impact of miRNA-mRNA interaction involved in the biological processes and to assist miRNA-based drug development in the future.